Ketamine prevents seizures and reverses changes in muscarinic receptor induced by bicuculline in rats - Schneider, Patricia Graciela (2013)
The cholinergic system has been implicated in several experimental epilepsy models. In a previous study bicuculline (BIC), known to antagonize GABA-A postsynaptic receptor subtype, was administered to rats at subconvulsant (1 mg/kg) and convulsant (7.5 mg/kg) doses and quinuclidinyl benzilate ([3H]-QNB) binding to CNS membranes was determined. It was observed that ligand binding to cerebellum increases while it decreases in the case of hippocampus. Saturation binding curves showed that changes were due to the modification of receptor affinity for the ligand without alteration of binding site number. The purpose of this study was to assay muscarinic receptors employing other BIC dose (5 mg/kg), which induces seizures and allows the analysis of a postseizure stage as well. To study further muscarinic receptor involvement in BIC induced seizures, KET was also employed since it is a well known anticonvulsant in some experimental models. The administration of BIC at 5 mg/kg to rats produced a similar pattern of changes in [3H]-QNB binding to those recorded with 1.0 and 7.5 mg/kg doses. Here again, changes were observed in receptor binding affinity without alteration in binding site number for cerebellum or hippocampus membranes. Pretreatment with KET (40 mg/kg) prevented BIC seizures and reverted [3H]-QNB binding changes induced by BIC administration. The single administration of KET invariably resulted in [3H]-QNB binding decrease to either cerebellar or hippocampal membranes. KET added in vitro decreased ligand binding likewise. Results of combined treatment with KET plus BIC are hardly attributable to the single reversion of BIC effect since KET alone invariably decreased ligand binding. It is suggested that besides alteration of cholinergic muscarinic receptor other(s) neurotransmitter system(s) may well also be involved.